Access to dental services and use of toothpaste with optimal fluoride content in Peruvian children - Hadad-Arrascue, Natalie; Garcés-Elías, María Claudia (Frontiers in Dental Medicine, 2024)
Background Leading international health organizations advise using toothpaste that contains at least 1,000 parts per million of fluoride, emphasizing that this practice should begin with the eruption of the first primary tooth. Aim To determine the association between access to dental services and the use of toothpaste with 1,000 ppm fluoride or more in Peruvian children under twelve years of age. Materials and methods A cross-sectional analysis was conducted using data from the 2021 Demographic and Family Health Survey. The main variable studied was the use of toothpaste containing a fluoride concentration of 1,000 ppm or more. Additionally, the access to dental care, the time elapsed since the last dental visit, and the type of healthcare facility were analyzed. Multilevel regression was applied to examine the relationship between variables and the dependent variable, with Peru's 24 regions serving as the analytical level. Results According to the bivariate analysis, the natural region, area of residence, place of residence, wealth index, and age were associated with the use of fluoride toothpaste with 1,000 ppm or more. In the multilevel analysis, the access to dental services was not associated with the use of fluoride toothpaste with 1,000 ppm or more (p = 0.454); similarly, the time elapsed since the last dental visit also showed no association (p = 0.676), as did the type of healthcare facility (p = 0.752, p = 0.896, p = 0.983). Conclusion Accessing dental services, the time elapsed since the last dentist visit, and the location where that care was received were not associated with the use of toothpaste containing 1,000 ppm or more of fluoride among Peruvian children during the year 2021.